How far is Shrimp Head Waste Utilized? An Overview of Environmental Innovation Management - Syahadat, Ray March; Zulfa, Nely (Indonesian Green Technology Journal, 2025)
This article aims to provide knowledge about the utilization of shrimp head waste in the perspective of environmental innovation management. The method was used by exploring articles through Google Scholar with Harzing's Publish or Perish software and using the keywords utilization of shrimp head waste. The article focuses on looking at the position slot777 of this topic in Indonesia as the largest archipelagic country in the world. Twenty articles published since 2019 were selected and analyzed descriptively. The results obtained, the processing of shrimp head waste can be grouped into three utilization groups. The three groups include: 1) utilization for agriculture, livestock, and fisheries, 2) utilization for food, and 3) utilization for other needs. In general, the processing of shrimp head waste for use is still in the form of products with low economic value. The suggested research direction in the future is shrimp head waste treatment, which has high economic value. The importance of this review is to provide knowledge on achieving environmental sustainability, particularly for Indonesia. It is also considered relevant for countries with coastal and island landscapes